A COMPARATIVE STUDY BETWEEN SANTULLI ILEOSTOMY AND LOOP ILEOSTOMY IN NEONATES WITH MECONIUM ILEUS - ASKARPOUR,Shahnam (2020)
ABSTRACT Background: Meconium ileus is a common cause of intestinal obstruction in neonates that different surgical methods have been described for its management such as Santulli and loop ileostomy. Aim: To evaluate and compare clinical efficacy of Santulli and loop ileostomy in neonates with meconium ileus. Methods: In this retrospective study, 58 patients with meconium ileus were evaluated. After analyses of hospital records, 53 patients with completed hospital records were included. Demographic information, surgery parameters and postoperative complications were extracted from the hospital records or calling parents. Results: Skin excoriation (21.4% vs. 84%, p<0.001), ostomy prolapsed (0 vs. 28%, p=0.003), and surgical site infection (7.1% vs. 28%, p=0.044) was significantly lower in Santulli ileostomy group. Furthermore, ileostomy output in first week (70.53±15.11 ml vs. 144.6±19.99 ml, p<0.001) and in 4th week (2.14±4.98 ml vs. 18.4±17.95 ml, p<0.001) was significantly lower in Santulli ileostomy group as compared to loop ileostomy group. Finally, hospital stay in Santulli ileostomy group was 12±2.34 and in loop ileostomy 14.24±1.47 days (p<0.001). Conclusion: Santulli ileostomy is better than loop ileostomy due to significant less frequency of surgical site infection, skin excoriation, prolapse of ostomy, ileostomy volume output and hospitalization time.